Selective extraction of Ascorbic acid by molecular imprinted polymer solid-phase extraction - Leila Baramakeh (Journal of Chemistry Letters)
A Highly sensitive and selective molecular imprinted polymer (MIP) was synthesized for solid phase extraction and preconcentration of trace amount of Ascorbic acid (AA). Parameters affecting separation and synthesis the polymer such as volume of the solvent, equilibration time, material selectivity and capacity, time, pH, … were checked by ultraviolet (UV) spectroscopy. Then the imprinted polymer applied for extraction of AA with solid-phase extraction, the process done with batch method. The selectivity of method was checked using some real samples. Linear range of the method was examined the data obtained showed linearity over the range of 0.4-9.0 mg/L.